Papillon-Lefevre syndrome with pseudoainhum - P Ashwani; K Swapna; M Sailaja Rani; B.S.N Reddy (Wolters Kluwer Medknow Publications, 2010)
An interesting episode of Papillon-Lefevre syndrome in a 25-year-old female with diffuse palmoplantar keratoderma, periodontitis and pseudoainhum of the toes is reported for academic interest. Her skin lesions improved with topical keratolytics and oral retinoid (acitretin) whereas periodontic problems showed significant improvement with systemic antibiotics and proper implementation of oral hygienic measures. She is undergoing oral rehabilitation with orthodontic surgical procedures.